Precarious Creativity Global Media, Local Labor - Curtin, Michael (University of California Press, 2016)
Precarious Creativity examines the seismic changes confronting media workers in an age of globalization and corporate conglomeration. This pathbreaking anthology peeks behind the hype and supposed glamor of screen media industries to reveal the intensifying pressures and challenges workers face. The authors take on crucial issues and provide insightful case studies of workplace dynamics regarding creativity, collaboration, exploitation, and cultural difference. Furthermore, they investigate working conditions and organizing efforts on all six continents, offering comprehensive analysis of contemporary screen media labor in places such as Lagos, Prague, Hollywood, and Hyderabad, across a range of job categories that includes visual effects, production services, and adult entertainment. With contributions from John Caldwell, Vicki Mayer, Herman Gray, Tejaswini Ganti, and others, this collection offers timely critiques of media globalization and broader debates about labor, creativity, and precarity. "Every case study is an eye-opener, and no other book comes close in assessing the plight of creative workers in the era of global conglomerate Hollywood." -THOMAS SCHATZ, University of Texas at Austin "A corrective to previous, U.S.-centric attempts to understand the global media economy by offering a bracing look at the dark underbelly of life for most media workers today." -DENISE MANN, University of California, Los Angeles "A balanced and comprehensive portrayal of the reshaping of the contours of work and industry organization under the twin circumstances of digital disruption and a globalizing media system." -TOM O'REGAN, The University of Queensland MICHAEL CURTIN is a professor of Film and Media Studies at University of California, Santa Barbara. KEVIN SANSON is a Lecturer in Entertainment Industries at Queensland University of Technology in Australia.